The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1080/02791072.1999.10471740
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Delirium After “Ecstasy” Ingestion

Abstract: Three cases of delirium experienced by three young friends after recreational use of "ecstasy" are reported--a syndrome which, to the best of the authors' knowledge, has not been previously observed in MDMA abusers. Special attention is given to the etiological factors and clinical features of the adverse reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Delirium, agitation and seizures should be controlled with increments of diazepam in the first instance, in preference to chlorpromazine [109,127]. In cocaine users it has been found that diazepam is less…”
Section: Treatment Of Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delirium, agitation and seizures should be controlled with increments of diazepam in the first instance, in preference to chlorpromazine [109,127]. In cocaine users it has been found that diazepam is less…”
Section: Treatment Of Adverse Effectsmentioning
confidence: 99%
“…The use of neuroleptics requires care because of the theoretical risk of producing the neuroleptic malignant syndrome and the possibility of precipitating seizures [68]. Delirium, agitation and seizures should be controlled with increments of diazepam in the first instance, in preference to chlorpromazine [109,127]. In cocaine users it has been found that diazepam is less…”
Section: Treatment Of Adverse Effectsmentioning
confidence: 99%
“…One month later, he developed a vegetative state and his MRI revealed diffuse bilateral extensive hypodense lesions of the white matter [13]. In 1999, an Italian research group reported delirium in three young adults after recreational ecstasy ingestion, but this study did not report brain image findings because the cases resolved rapidly [14] (Table 1). In 2012, Sacks and colleagues reported a case of 26-year-old male patient who presented with unconsciousness after an overdose with "Europa = 2C-E," an MDMA-related drug.…”
Section: Discussionmentioning
confidence: 40%
“…A high dose or an overdose of Ecstasy poses the risks of acute delirium, acute anxiety reactions, malignant hyperthermia, rhabdomyolysis, acute kidney failure, syndrome of inappropriate antidiuretic hormone, bilateral sixth nerve palsy, cardiovascular abnormalities, seizure, cerebral edema, coma, and death. 13,15,[17][18][19][20] Of all the acute complications, hyperthermia is particularly important since it could lead to seizure and coma. Factors that induce hyperthermia include dehydration, alcohol consumption, physical exertion, and heat, all of which are present at rave clubs.…”
Section: Adverse Effectsmentioning
confidence: 99%